1997
DOI: 10.1136/thx.52.1.38
|View full text |Cite
|
Sign up to set email alerts
|

British Thoracic Society study of cryptogenic fibrosing alveolitis: current presentation and initial management. Fibrosing Alveolitis Subcommittee of the Research Committee of the British Thoracic Society

Abstract: Abstractprognosis. Physicians generally considered CFA to be a clinical diagnosis and Background -Mortality due to cryptodid not initiate treatment in up to half of genic fibrosing alveolitis (CFA) is inpatients at presentation. creasing, particularly in the elderly. (Thorax 1997;52:38-44) Optimum management remains uncertain and previous studies of the disease have Keywords: cryptogenic fibrosing alveolitis, presentation, largely been from specialist centres. A treatment, British Thoracic Society.national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
139
2
9

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(155 citation statements)
references
References 11 publications
5
139
2
9
Order By: Relevance
“…In one series, only 12% of patients with suspected CFA underwent OLB. Age and poor lung function were the most important factors that led to the decision to avoid this investigation [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one series, only 12% of patients with suspected CFA underwent OLB. Age and poor lung function were the most important factors that led to the decision to avoid this investigation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Longer-term effects such as those on lung function have not been studied. It has been suggested that lung biopsy may cause a deterioration in lung function and this may partly explain the reluctance of many physicians in the UK to include lung biopsy in the evaluative process [10]. The goals of the present study were to examine the effects of lung biopsy on lung function and to compare the consequences of OLB and VATS.…”
mentioning
confidence: 99%
“…The most common clinical presentation of IPF is that of insidious progressive shortness of breath, or dyspnea, being present for at least 3 to 4 months. 3,4,51 Cough may be present with or without sputum. 3,4,51 On physical examination 25%-50% of patients with IPF have evidence of clubbing.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…3,4,51 On physical examination 25%-50% of patients with IPF have evidence of clubbing. [3][4][5]51 The presence of clubbing is helpful in suggesting a diagnosis of 4 ‡Clinical disorder that corresponds to the histological pattern indicated on the left. 4 §Provisional nomenclature subject to further classification.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The inheritance pattern is most consistent with autosomal dominant with incomplete penetrance. The clinical presentation of familial IPF is indistinguishable from sporadic IPF except that the age of onset tends to be earlier (55 years vs. 67 years) (4,5). Here we report the use of a genetic linkage approach to map the culprit gene in two large families to chromosome 5.…”
mentioning
confidence: 99%